2022
DOI: 10.2147/jmdh.s362550
|View full text |Cite
|
Sign up to set email alerts
|

From “Cure” to “Care”: The Role of the MultiDisciplinary Team on Colorectal Cancer Patients’ Satisfaction and Oncological Outcomes

Abstract: Background: MultiDisciplinary Team (MDT) are held to undertake decisions regarding the whole aspect of oncological diseases. Over the years, they acquired a collaborative approach where clinical decisions are shared by all members. Different guidelines recommend the implementation of MDT, in order to improve the outcomes of these patients. Our aim is to evaluate how the implementation of MDT affects the patients' satisfaction and adherence to treatment. Methods: A survey was submitted to every patient affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Ideally, the MDT should encompass experts in colorectal surgery, gastrointestinal surgery, hepatic surgery, medical oncology, radiation oncology, interventional radiology, radiology, ultrasound imaging, pathology, and other pertinent specialties. This collaborative and comprehensive team ensures a holistic evaluation of each patient, allowing for a well-rounded and specialized treatment plan that considers the intricacies of CRLM from various medical perspectives[ 38 ].…”
Section: The Crucial Role Of Mdt In Customizing Individualized Approa...mentioning
confidence: 99%
“…Ideally, the MDT should encompass experts in colorectal surgery, gastrointestinal surgery, hepatic surgery, medical oncology, radiation oncology, interventional radiology, radiology, ultrasound imaging, pathology, and other pertinent specialties. This collaborative and comprehensive team ensures a holistic evaluation of each patient, allowing for a well-rounded and specialized treatment plan that considers the intricacies of CRLM from various medical perspectives[ 38 ].…”
Section: The Crucial Role Of Mdt In Customizing Individualized Approa...mentioning
confidence: 99%
“…Despite better knowledge about the risk factors of AL identified over the years [7, 8] and advances in surgical techniques and in perioperative management [9], AL after rectal cancer surgery remains a significant problem. It has been demonstrated that AL will result in a longer hospital stay, increased hospitalization costs, delay to postoperative chemotherapy, a poorer functional result [10], an increased local recurrence rate and shortened overall survival [11–16].…”
Section: Introductionmentioning
confidence: 99%
“… 26–28 As shown by international research, consideration of patient preferences in MTCs can lead to better patient outcomes and better adherence to MTC recommendations. 20–22 …”
Section: Introductionmentioning
confidence: 99%
“…14,15 Although important research on the degrees of multidisciplinarity in MTCs is still ongoing, 15,16 MTCs are related to increased diagnostic and treatment options and therefore have been implemented in oncology in many countries worldwide. 14,[17][18][19][20][21][22] On the basis of the outlined developments of SDM and multidisciplinary health care, some authors have investigated the extent of patient-centeredness of MTCs. [23][24][25] In this context, studies demonstrated that the consideration of patient preferences differed between MTCs and that the discussion often strongly focusses on biomedical information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation